Cronhova bolezen - Gošnjak, Tanja (Placebo, 2022)
Crohn's disease is an idiopathic chronic inflammatory disease that can affect any part of the gastrointestinal tract and is immune-mediated. It most commonly affects the terminal ileum and colon. There are several risk factors for developing Crohn's disease, including genetic susceptibility, altered microbiota, and environmental factors. Common symptoms include abdominal pain, diarrhea, weight loss and fatigue. Diagnosis of the disease is based on endoscopy and histological analysis of an intestinal sample. In addition, tests using less invasive biomarkers are being developed. The goal of treatment is to reduce inflammation and improve prognosis by limiting disease complications.
Keywords: biološki označevalci; biomarkers; Crohnova bolezen; Crohn's disease; inflammation; inflammatory bowel disease; Kronična vnetna črevesna bolezen; pathophysiology; Patofiziologija; vnetje